2012
DOI: 10.1007/s11606-012-2003-y
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Patient- and Medication-Related Factors on Inpatient Medication Reconciliation Errors

Abstract: BACKGROUND:Little research has examined the incidence, clinical relevance, and predictors of medication reconciliation errors at hospital admission and discharge. OBJECTIVE: To identify patient-and medication-related factors that contribute to pre-admission medication list (PAML) errors and admission order errors, and to test whether such errors persist in the discharge medication list. DESIGN, PARTICIPANTS: We conducted a crosssectional analysis of 423 adults with acute coronary syndromes or acute decompensat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 31 publications
(68 reference statements)
6
60
3
2
Order By: Relevance
“…According to the NCCMERP classification, the majority of the errors (80%) was classified as B category (the error occurs, but does not reach the patient), followed by class C (15%) (the error reach the patient, but does not cause harm). Omission errors were also the most frequent problem identified by many authors (Lubowski et al, 2007;Pippins et al, 2008;Salanitro et al, 2012;Hellstrom et al, 2012). Dosing errors level is also in accordance with the literature (Pippins et al, 2008;Stone et al, 2010).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…According to the NCCMERP classification, the majority of the errors (80%) was classified as B category (the error occurs, but does not reach the patient), followed by class C (15%) (the error reach the patient, but does not cause harm). Omission errors were also the most frequent problem identified by many authors (Lubowski et al, 2007;Pippins et al, 2008;Salanitro et al, 2012;Hellstrom et al, 2012). Dosing errors level is also in accordance with the literature (Pippins et al, 2008;Stone et al, 2010).…”
Section: Resultssupporting
confidence: 87%
“…However, other studies found a lower proportion of harm related to drug errors. BecerraCamargo et al (2013) considered that only 42.7% of the errors could lead to a patient discomfort and Salanitro et al (2012) pointed out that only 59% of the errors could result in harm for the patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the frequency of omission (27%) and commission (36%) errors are similar to what we have reported in the PILL-CVD study, which enrolled a comparable inpatient population. 39 Furthermore, 41% of patients in the current study correctly reported the indication, dose, and frequency for tested cardiac medications. Prior studies have reported each outcome individually: 64-79% of patients reported the correct indication, 40,41 56% the correct dosage, 40 and 68% the correct frequency.…”
Section: Commentsmentioning
confidence: 62%
“…1 In 2006, the World Health Organisation initiated the High 5 s Project where it recommended medication reconciliation to prevent medication errors at transition points. 2 Purpose To implement and evaluate a clinical pharmacist-led medication reconciliation service in geriatric patients upon admission to hospital, in terms of frequency, type and potential severity of the medication errors identified.…”
Section: References And/or Acknowledgementsmentioning
confidence: 99%